PERCEPTION OF PULMONARY TB PATIENTS ON TREATMENT WITH DIRECTLY OBSERVED TREATMENT SHORT COUSE (DOTS) STRATEGY IN THE UPTD AREA OF THE SERBELAWAN SIMALUNGUN DISTRICT PUSKESMAS IN 2020 - Pakpahan, Romauli; Feinberg, Bob; Doortua, Doortua; Maswan, Maswan; Lubis, Josep (Universitas Efarina, 2021)
TB sufferers and minimize the chain of transmission of pulmonary tuberculosis and especially health workers / health center nurses. Serbewan to always provide information and counseling about pulmonary tuberculosis.